Coping in Times of Uncertainty and Global Risks: The Main Research Trends - Belinskaya, E. P. (Вестник Кемеровского государственного университета, 2022)
This article reviews foreign and domestic publications on the psychology of coping. Until the early XXI century, coping studies followed three research lines: 1) situations perceived as "difficult", 2) coping strategies and/or styles, 3) their relationships with personal and environmental coping resources. The current global situation of uncertainty and risks has affected the strategy of coping studies. They now demonstrate a more complex and holistic vision of the interaction between the person and the situation that requires coping. The interaction pattern follows three main research trends: 1) Personal coping resources are understood not as specific personal dispositions or cognitive characteristics, but as complex features that require new research methods; 2) New empirical material proves the ambiguity of correlation between various human coping strategies and psychological well-being; 3) Procedural features of coping and its anticipatory capabilities acquire more scientific attention.